Research on 5G upstream bandwidth detection technology and application - Guobin XU; Zhewei FU; Ming LIU; Zhiji DENG; Cungang WANG; Guanghai ZHONG; Hui LI; Wei MENG; Yunjie WU (Dianxin kexue)
A scheme of 5G upstream bandwidth detection technology and application was proposed, which could effectively solve the problem of 5G network fluctuation in video monitoring data transmission process.It will help the deployment of 5G video monitoring application.By obtaining the radio resource information of 5G NR, the terminal can count the transmission resource and estimate the change trend of uplink bandwidth.Combined with the intelligent coding technology and bit-stream adaptive technology of streaming media application, the scheme ensures no stuck and continuous picture at the cost of losing a little video definition, and ensures the overall experience of customers.The scheme can be widely used in the scene of heavy 5G public service, large network fluctuation and wide network coverage, such as campus video surveillance.